Guide to Foresters in Investigating Forest Diseases - Bakshi, B. K. (Indian Forester, 1959)
Causes of forest diseases, their symptoms, effects on trees and mode of spread are described in order to enable foresters to report on them and send suitable material to the specialist for further investigation.